2020
DOI: 10.1186/s12886-020-01507-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypothermic perfusion on phacoemulsification in cataract patients complicated with uveitis: a randomised trial

Abstract: Background: To evaluate the effectiveness and safety of hypothermic perfusion in the phacoemulsification of cataract caused by uveitis. Methods: This was a prospective, single-masked, randomised, controlled clinical trial. One hundred and six patients with uveitis-associated cataract underwent phacoemulsification with perfusion fluid temperature at 4°C (treatment group) or 24°C (control group). Anterior chamber inflammation grade, corneal endothelial cell count, corneal thickness, macular fovea thickness, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…As one of the diseases causing blindness, uveitis has hundreds of causes, but the associated etiological mechanism remains undefined, making treatment challenging; cataract is its most common complication [1] . Patients with anterior uveitis or intermediate uveitis experience repeated recurrence and longterm inflammatory response that leads to inflammatory cell infiltration to the lens capsule, affecting its permeability, with altered composition of aqueous fluids affecting lens metabolism that causes the cataract complication; meanwhile, patients with posterior uveitis develop cataract as a result of long-term intake of glucocorticoid drugs in addition to inflammatory causes [9] . The preferred surgical method for uveitis-induced cataract is phacoemulsification in conjunction with IOL implantation.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the diseases causing blindness, uveitis has hundreds of causes, but the associated etiological mechanism remains undefined, making treatment challenging; cataract is its most common complication [1] . Patients with anterior uveitis or intermediate uveitis experience repeated recurrence and longterm inflammatory response that leads to inflammatory cell infiltration to the lens capsule, affecting its permeability, with altered composition of aqueous fluids affecting lens metabolism that causes the cataract complication; meanwhile, patients with posterior uveitis develop cataract as a result of long-term intake of glucocorticoid drugs in addition to inflammatory causes [9] . The preferred surgical method for uveitis-induced cataract is phacoemulsification in conjunction with IOL implantation.…”
Section: Discussionmentioning
confidence: 99%
“…4 Jiang et al observed the effect of hypothermia perfusion in the phacoemulsification of uveitis-associated cataracts and found that the mean percentage of hexagonality was higher in the 4 0 C group than the 24 0 C group at 7 days postoperatively but not statistically significant between the two groups. 10 Our results showed that intraocular hypothermic perfusion had no significant effect on changes in CV and hexagonality. This result does not follow our hypothesis, where the change in CV and hexagonality is lower in hypothermic conditions.…”
Section: Original Articlementioning
confidence: 46%
“…4 Jiang et al reported hypothermic perfusion in uveitisassociated cataracts could inhibit anterior segment inflammation and reduce corneal edema. 10 The present study aims to assess the effect of hypothermic perfusion on the corneal endothelium during the phacoemulsification process by evaluating SOD1 expression and morphological changes in corneal endothelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Epithelial edema can occur if excessive local anesthetics or ultrasound vibration is used during phacoemulsification. The integrity of both the epithelial and endothelial layers is critical to keeping corneal deturgescence and a balanced stroma hydration [1,10,21,23,30,45,68,69].…”
Section: Endothelial Cell Loss (Ecl)mentioning
confidence: 99%
“…Precautions must be taken during phacoemulsification to avoid corneal edema caused by trauma phacoemulsifiers, lens hardness, short anterior chamber depths, retained viscoelastic fragments of the lens, irrigating solutions and their temperature, phacoemulsification time and energy, IOL insertion, and the surgeon's expertise, which is especially important in patients with pseudoexfoliation or previous endothelial damage (guttae) [6,9,12,17,34,44,45,47,50,65,98,99].…”
Section: Mechanical Traumamentioning
confidence: 99%

Corneal Edema after Cataract Surgery

Briceno-Lopez,
Burguera-Giménez,
García-Domene
et al. 2023
JCM